Vertical jumping performance relates to the one-repetition maximum in the standing calf raise and in the squat - Möck, S.; Hartmann, R.; Wirth, K. (German Journal of Exercise and Sport Research, 2023)
Vertical jumping performance is of high importance for various individual and team sports. Movement patterns utilizing a stretch shortening cycle are of particular interest. Despite their involvement in every vertical jump variation, the importance of the plantar flexors` dynamic maximum strength for jumping performance has not been investigated yet. Therefore, the aim of this study is to examine the relationship between plantar flexion strength and different vertical jump variations. The present study examines the correlation of maximum strength in the standing calf raise and in the squat with performance in the vertical jumping forms squat jump (SJ), countermovement jump (CMJ), and drop jump (DJ) from different heights in 56 physical education students. The one-repetition maximum (1RM) in the standing calf raise shows moderate to high (p< 0.01) correlations for SJ and CMJ (r= 0.575-0.659, and r= 0.565-0.708, respectively). The DJ revealed weak to medium correlations (p< 0.01) with the dynamic maximum strength of the plantar flexors (r= 0.362-0.573). A comparison of the strongest and weakest subjects revealed significant differences between groups with the stronger participants displaying greater jumping performance in all tests. In addition, squat 1RM was significantly correlated (p< 0.05) with DJ performance. It can be concluded that the strength of the plantar flexors displays a relevant factor for vertical jumping performance in SJ, CMJ, and DJ that supports the main propulsive mechanisms.